Amin is attempting to solve the following equation. (x+1)(x+4)=(x-2)(x-3) solve the equation

Question

Amin is attempting to solve the following equation. (x+1)(x+4)=(x-2)(x-3) solve the equation

in progress 0
Vân Khánh 6 months 2021-08-04T12:14:09+00:00 2 Answers 20 views 0

Answers ( )

    0
    2021-08-04T12:15:27+00:00

    Step-by-step explanation:

    Hey there!

    Given;

    (X+1) (X+4) = (x-2) (x-3)

    Multiply (X+1) and (X+4) on left side and (x-2) and (x-3) on right side.

     {x}^{2}  + 4x + x + 4 =  {x}^{2}  - 3x - 2x + 6

    Simplify it.

    5x  + 4 =  - 5x + 6

    10x = 6 -4

    x =  \frac{2}{10}

    Therefore, x= 1/5.

    Hope it helps....

    0
    2021-08-04T12:15:32+00:00

    Answer: x = 1/5

    After expanding, (x+1)(x+4) = (x-2)(x-3) becomes x² + 5x + 4 = x² – 5x + 6. Subtracting x² and adding 5x to both sides, we have 10x = 2 and x = 1/5. You can plug this in to check.

    i hope this was helpful! 😀

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )